2004
DOI: 10.1023/b:glyc.0000045095.86867.c0
|View full text |Cite
|
Sign up to set email alerts
|

Ligands of the asialoglycoprotein receptor for targeted gene delivery, part 1: Synthesis of and binding studies with biotinylated cluster glycosides containing N-acetylgalactosamine

Abstract: In order to develop the non-viral Bioplex vector system for targeted delivery of genes to hepatocytes, we have evaluated the structure-function relationship for a number of synthetic ligands designed for specific interaction with the hepatic lectin ASGPr. Biotinylated ligand derivatives containing two, three or six beta-linked N-acetylgalactosamine (GalNAc) residues were synthesized, bound to fluorescent-labeled streptavidin and tested for binding and uptake to HepG2 cells using flow cytometry analysis (FACS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…(5). These ligands, tested in vivo, differ greatly from the ones described above by Westerlind et al [61], and are less efficient in receptor binding due to steric hindrance, suboptimal orientation and geometry of the terminal sugars (data not shown). In this experiment no difference in liver distribution was seen when comparing the GalNAc and Gal FEs.…”
Section: Utilising the Asgp Receptor For Liver Targeted Bioplexmentioning
confidence: 70%
See 3 more Smart Citations
“…(5). These ligands, tested in vivo, differ greatly from the ones described above by Westerlind et al [61], and are less efficient in receptor binding due to steric hindrance, suboptimal orientation and geometry of the terminal sugars (data not shown). In this experiment no difference in liver distribution was seen when comparing the GalNAc and Gal FEs.…”
Section: Utilising the Asgp Receptor For Liver Targeted Bioplexmentioning
confidence: 70%
“…Westerlind et al [61] showed that synthetic ligands containing trimetric units of GalNAc bound to fluorescentlabelled streptavidin exhibit high binding affinity and specific uptake in the HepG2 hepatocyte cell line. Furthermore, they demonstrated that the uptake could be blocked with EDTA, which chelates the divalent calcium ions, thus inhibiting binding of the calcium dependent ASGPr.…”
Section: Utilising the Asgp Receptor For Liver Targeted Bioplexmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, among the structures proposed for optimal ASGP‐R recognition are tripods bearing, on each arm, a β‐linked GalNAc moiety kept about 20 Å away from the branching point of the tripod by an ethylene glycol spacer . The tripodal architecture of L 2 is thus perfectly suitable for the design of the triantennary glycoside cluster Chel2 (Fig.…”
Section: A Glycoconjugate That Releases a High‐affinity Cu(i) Chelatomentioning
confidence: 99%